Cu(II)/Vasicine Promoted Intramolecular C-O Formation: Synthesis of Benzoxazoles in EtOH - Li, Minxin; Li, Meiling; Tang, Yanling; Sun, Yun; Qu, Lu; Mao, Zewei (Current Organic Synthesis, 2021)
Aims and Objectives: Benzoxazoles are valuable bicyclic aromatic compounds; the construction of benzoxazoles via C-O cross-coupling reactions has attracted more and more attention. Materials and Methods: The best condition of C-O bond formation from o-haloanilides was carried out, taking Cu(OTf)2 (5 mol%) and vasicine (10 mol%) as the catalysts in EtOH in the presence of K2CO3 (2 eq.) for 12 h at 90°C. Results: A series of 2-substituted benzoxazoles have been prepared in high yields from 2-bromoanilides and 2- iodioanilides under mild conditions. Conclusion: We have developed an efficient Cu-vasicine catalytic system for intramolecular C-O bond formation. This strategy is applicable to the synthesis of a wide variety of 2-substituted benzoxazoles by intramolecular O-arylation of o-haloanilides.
Keywords: benzoxazoles